Extraction of Maxillary Central Incisors: An Orthodontic-Restorative Treatment - Zohreh Hedayati; Maryam Zare; Fateme Bahramnia (Case Reports in Dentistry)
Malformed central incisors with poor prognosis could be candidates for extraction especially in crowded dental arches. This case report refers to a 12-year-old boy who suffered from malformed upper central incisors associated with severe attrition. Upper lateral incisors were positioned palatally and canines were rotated and positioned in the high buccal area. The patient had class II malocclusion and space deficiency in both dental arches. Due to incisal wear and malformed short maxillary central incisors and the need for root canal therapy with a major crown build-up, these teeth were extracted. The maxillary lateral incisors were substituted. Thus the maxillary canines were substituted for lateral incisors and the first premolars were substituted for canines. In the lower dental arch the first bicuspids were extracted. Composite resin build-up was performed on the maxillary lateral incisors and canines. This allowed for the crowding and the malocclusion to be corrected. Subsequent gingivectomy improved the patient's gingival margins and smile esthetics one month after orthodontic therapy.